Perspectives on cytokine-directed therapies in multiple sclerosis (Swiss Medical Weekly, 2015)
Multiple sclerosis (MS) is the most common inflammatory demyelinating disorder of the central nervous system (CNS). Over the past 10 years there has been a heated debate as to whether MS pathogenesis commences in the CNS or whether it is actually primarily a disease of the immune system. The combined clinical data, therapy responses, pathology, animal models and genetic studies now provide overwhelming support for the concept that MS is a disease of the immune system and that the CNS is only the unfortunate target of a misguided immune attack. Immune cells communicate through the use of cytokines and these proteins can orchestrate the most complex behaviour in immune cells. We propose that MS is a disease where immune communication is derailed, which makes MS very amenable to immunotherapy and in particular makes cytokines an attractive target to repair this miscommunication disorder.